Kegiatan Pendampingan Untuk Menggali Nilai Tradisional Dalam Matematika Di Kota Pekalongan: Peningkatan Wawasan Motif Batik Melalui Etnomatematika - Vila Sufia, Nila; Mahmudah, Umi; Munawaroh, Zakiyatul; Fitrotunnida, Tsania (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
This article discusses mentoring activities in order to increase public knowledge about the integration of cultural values and mathematical concepts. The activity was attended by 30 participants from various groups in Pekalongan City in January 2023. The activity method includes planning, implementing, and monitoring. The results of the activity show that there are various mathematical concepts in Pekalongan batik motifs, namely the concept of symmetry in the Parang Rusak motif; repeating patterns in the Kawung motif, geometry in the Tantrum motif design; proportions in the Slope motif, measurements and calculations in the Sido Mukti motif. This activity is expected to increase appreciation of local culture and integrate ethnomathematics in learning and everyday life. This activity contributes to the preservation of Pekalongan's cultural heritage and enriches mathematics learning with relevant cultural values.